Commitment and the new employment relationship: Exploring a forgotten perspective. Employers commitment - Nicole Torka; Jan Kees Looise; Maarten van Riemsdijk (Management Revue, 2005)
In this article, we have endeavoured to integrate the concept 'employers' commitment' into the understanding of the new employment relationship. HRM scholars and practitioners assume that changes in (international) market and employee characteristics lead to a transformation of the employer-employee relationship: from a life-long, 'steady' relationship to life-time employability based on diminished job-security and enhanced employer and employee investments in training and development. We examine employees' internalisations with respect to this new relationship, or at least their identification with it. 'Employers commitment', a concept that has been neglected empirically to a large extent in management and work sciences, serves as the backbone of our argument, and refers to the commitment the employee receives from the employer. From the workers' perspective, 'employers' commitment' has everything to do with 'traditional' expectations about social aspects of the employer-employee relationship and with (individualised) employment relations. Concerning the latter, adequate 'direct participation' is the key. Since none of the employees mentioned any dimension of the so-called 'new deal' (e.g. job insecurity, training and career development, mobility) while describing their interpretation of 'employers commitment', (further) food for thought concerning the balance of the contemporary connection between employer and employee connection is presented.
Keywords: 650; employment relationship; reciprocity; employee commitment; employer commitment; Arbeitsbeziehungen